A parametric study of the thermo-pneumatic microvalve performance for microfluidic platforms: A finite element analysis - Alireza Mohseni; Mohammad Amin Ebrahimzadeh; Amirsaman Bahramian; Esmail Pishbin (Results in Engineering, 2025)
The optimization of thermo-pneumatic microvalves (TPMs) remains a significant challenge in microfluidic device development, primarily due to the complex interactions between various design parameters. This study presents a comprehensive numerical investigation of TPM performance through advanced fluid-structure interaction modeling. We systematically analyzed four critical design parameters: heating chamber geometry, gas composition, working fluid properties, and membrane materials. Our results reveal that an inward-angle heating chamber configuration substantially improves membrane deflection, generating a maximum applied pressure of 2702 N/m²—more than twice that of conventional straight-wall designs (1216 N/m²). We identified an optimal heating chamber aspect ratio of approximately 10, maximizing membrane deflection while maintaining structural integrity. Notably, the introduction of auxetic materials for membrane construction demonstrated a two-fold increase in deflection compared to traditional polyimide membranes. Analysis of working fluid properties showed that viscosity, rather than density, predominantly influences valve performance, with a three-order-of-magnitude increase in viscosity reducing deflection by 30 %. Furthermore, the molecular weight of the heating chamber gas emerged as a crucial factor, as evidenced by CO₂ producing eight times greater deflection than H₂. These findings provide valuable quantitative guidelines for optimizing TPM design in microfluidic applications, particularly for lab-on-a-chip devices and biomedical systems.